More about picture-changed vertices in superstring theory - Pettorino, R; Pezzella, F (1991)
We construct explicitly the lowest picture-changed vertex operators in superstring theory. We show, in particular, that the terms with (b, c) ghost number q=1 are of the form c(z) V(z) as the vertex operators in the bosonic string case.